Formation Process of Derived Words in Malay and Iban - Jimbai, Jackson; Banseng, Saripah; Handrianto, Ciptro (International Journal of Education, Information Technology, and Others, 2024)
The Study on the Formation Process of Derived Words in Malay and Iban is a bilingual research that aims to study the process of forming derived words in Malay and Iban while also discussing the differences that occur from the aspect of morphemes that form derived words for both languages. The method used is entirely a qualitative method by highlighting document analysis instruments and checklist forms. Some derived word lists are taken from the Kamus Dewan Edisi Keempat and Bup Sereba Reti. The data obtained is released in the form of a checklist table to display the comparison, especially the difference aspects of Malay and Iban derived words. In order to see the word formation process that takes place, Tatabahasa Dewan, Nahu Melayu Mutakhir and Iban Language Morphology are used as data sources. The findings state that all derived words with the same meaning in Malay Language and Iban Language are combined with different morphemes to form prefixes, suffixes and affixes. The word class transformation process based on Minimalist Theory also states that there are significant differences for derived words built in simple sentences. Malay does not go through the root word level for word production while Iban language can go through root words and base words. This study can establish a limitation between Malay Language and Bahasa Iban which have similarities in terms of language systems. It is hoped that this study will have an impact on language scholars as a stepping stone to continue other researches, especially studies in the form of comparisons between two languages that have correlations and kinship relationships.